Bacterial hyaluronic acid production through an alternative extraction method and its characterization. Issue 6 (25th March 2019) - Güngör, Gökhan; Gedikli, Serap; Toptaş, Yağmur; Akgün, Dilber E; Demirbilek, Murat; Yazıhan, Nuray; Aytar Çelik, Pınar; Denkbaş, Emir B; Çabuk, Ahmet
Abstract: BACKGROUND: In this study, hyaluronic acid (HA) was produced using Streptococcus equi ssp. equi via an optimized Central Composite Design process, with purification by an alternative extraction method. Determinations of molecular weight, cytotoxicity, viscosity; proton nuclear magnetic resonance (H‐NMR) and Fourier transform infrared‐attenuated total reflection (FTIR‐ATR) analyses were provided. RESULTS: The HA yield obtained was up to c . 12 g L −1 under the reaction conditions of pH 7.8, 33 °C incubation temperature, 24 h incubation time and 187 rpm agitation rate. According to gel permeation chromatography results, HA has an average molecular weight of 79 416 Da. FTIR‐ATR analysis showed that the spectrum of the standard HA sample overlapped with the spectrum obtained from this study. CONCLUSION: In this study, higher titer production of HA was obtained with a simple and economical sequential process. Additionally, the results indicate that the HA produced is an appropriate biomaterial for medical applications. © 2019 Society of Chemical Industry